Dental Implant Survival after Postoperative Infection - Iman Baig, Talha Bin Mushtaq, Batool Sajjad, Waheed Gul Shaikh, Maria Noor, Waqar Ali, Shaista Zafar (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: Dental implant failure might be brought on by an early postoperative infection. The purpose of this study was to assess the prevalence of acute postoperative infection in survived and failed implants and the associated factors. Methods: This cohort cross-sectional study held in the Oral surgery department of Altamash Institute of Dental Medicine, Karachi for two-years duration from January 2021 to December 2022 and evaluate early postoperative infection after dental implant surgery. The location of the implant, the patients’ ages and genders, smoking, postoperative antibiotic therapy, bone augmentation and the time of infection development or diagnosis were among the study variables. The study’s results showed which implants failed and which survived. Two groups of patients; those who survived implants included in Group A and those who had failed implants were included in group B. Results: Out of 190 patients, 12 (6.3%) patients, including 8 men and 4 women, experienced a postoperative infection after implant insertion. In group A of implant survival, 5 implants (41.7%) acquired post-operative infection while 7 implants (58.3%) in the failed group experience infections. The significant variations among the both groups were noted in terms of the smoker patients, the timing of diagnosis, patients who got bone transplant and fresh socket versus delayed implant placement. Relating to the variables, the Kaplan-Meier analysis revealed that when infection developed 4 days after surgical procedure in subjects not given antibiotic treatment postoperatively, the probability of implant failure increased by 1.1 times (hazard ratio). If the infection developed after six days in people who smoked and after nine days in people who do not smoked and were given antibiotics postoperatively, the likelihood of failure rose. Conclusion: In light of the study’s findings, it appears that smoking, early infection, implants placement in newly created sockets, and implants placement in conjunction with bone substitutes may all enhance the failure ratio of dental implants following acute infection. Keywords: antibiotic, implant, infection, and bone